2016
DOI: 10.7567/jjap.55.102302
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of encapsulants for photovoltaic modules made of ethylene vinyl acetate studied by positron annihilation lifetime spectroscopy

Abstract: The structure of ethylene vinyl acetate (EVA) encapsulants of crystalline-Si photovoltaic modules after the damp heat (DH) test was evaluated by positron annihilation lifetime spectroscopy (PALS). A reduction in free-volume hole size, which indicates the progress of deacetylation, was observed after the DH test. The difference in lifetime (Δτ) between the initial and DH-tested samples clearly increased after the DH test for 3000 h. The increase in Δτ was correlated with the acetic acid concentration in the EVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In a module constructed with a breathable backsheet, acetic acid is able to diffuse out of the module, resulting in a module pH environment between 4.76 and 7.0, which seems to agree with attempts to measure the pH of DH‐exposed EVA 59 . Acetic acid concentrations of several thousand ppm have been detected in DH‐aged EVA using various characterization methods 28,60 . Others have found that the precise level of EVA hydrolysis and corrosion depends on the degree of crosslinking of EVA, which seems to impact both the generation and out‐diffusion of acetic acid 39 .…”
Section: Resultssupporting
confidence: 71%
“…In a module constructed with a breathable backsheet, acetic acid is able to diffuse out of the module, resulting in a module pH environment between 4.76 and 7.0, which seems to agree with attempts to measure the pH of DH‐exposed EVA 59 . Acetic acid concentrations of several thousand ppm have been detected in DH‐aged EVA using various characterization methods 28,60 . Others have found that the precise level of EVA hydrolysis and corrosion depends on the degree of crosslinking of EVA, which seems to impact both the generation and out‐diffusion of acetic acid 39 .…”
Section: Resultssupporting
confidence: 71%
“…This reduction in τ correlated with the reduction in P max as well as the appearance of a dark region in the EL image of a PV cell. 15) The depth profile of τ of the Initial sample indicated that τ at a low E was smaller than that at a high E. This dependence on E may be attributable to the difference in the EVA structure between the surface and the inside of the EVA encapsulants, such as crosslinking density. The depth profile also revealed that a reduction in τ caused by aging was noticeable near the surface region of the Si cell side.…”
Section: Estimation Of Acetic Acid In Degraded Module By Ion Chromato...mentioning
confidence: 92%
“…31,32) Each of the near-surface regions, which were identified as the glass side or the Si side of an EVA encapsulant affixed to the cover glass or the Si cell, respectively, was examined as described in a previous work. 15) To obtain the depth profiles of τ, the incident positron energy was set sequentially at 1, 1.5, 2, 3, 4, 5, 6, and 8 keV. Two million annihilation events were collected for the measurement of each EVA sample.…”
Section: Estimation Of Acetic Acid In Degraded Module By Ion Chromato...mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Therefore, much effort has been devoted to developing novel acceleration tests that reproduce the degradation processes occurring in the field. 11,12) One of the origins of chemical corrosion degradation of crystalline Si (c-Si) PV modules is acetic acid [13][14][15][16][17][18][19] generated in the modules by hydrolysis reaction between water vapor 20,21) and an ethylene-vinyl acetate (EVA) encapsulant. It was reported in detail that the glass frit layer at the interface between the Ag finger electrodes and the Si emitter layer is dissolved by acetic acid, 22) and contact resistance is increased with the reduction in fill factor (FF) in the first stage and in short-circuit current (I sc ) in the second stage.…”
Section: Introductionmentioning
confidence: 99%